Globalisation and the Future of the Welfare State - Yu-Fu Chen; Holger Görg; Dennis Görlich; Hassan Molana; Catia Montagna; Yama Temouri (Institute for the Study of Labor (IZA), 2014)
This paper reconsiders the link between welfare state provision, globalisation and competitiveness empirically. We challenge the conventional wisdom that welfare states, large-scale public provision of social insurance and progressive systems of redistributive taxation are incompatible with economic globalisation. Our empirical analysis is motivated by recent theoretical work that looks at the effects of redistribution policies in open economies models that capture the interconnectedness of welfare states, production structures and international economic integration when goods and factor markets are imperfectly competitive and countries possess specific characteristics e.g. demographic structure, institutional features of labour markets, and government's preference structure. Hence, contrary to the conventional view, the efficiency gains stemming from increasing international openness strengthen the positive feed-back effects between redistribution policies and the exploitation of aggregate scale economies. We find some evidence in line with the theory, suggesting that there is indeed a positive interaction between vertical linkages and social expenditure in raising competitiveness. We also look at an important aspect of globalisation, namely the activities of multinational companies, and investigate whether social expenditure, which arguably contributes to a stable and more attractive social and economic environment for the operations of businesses, hinders or attracts inward investors. We find that social expenditure may be attractive to inward FDI and may also act to anchor firms in the home country.
Keywords: F6; H5; 330; welfare state; globalisation; economies of scale